Exon-skipping splice variants of excitatory amino acid transporter-2 (EAAT2) form heteromeric complexes with full-length EAAT2. - Gebhardt, FM; Mitrovic, AD; Gilbert, Daniel; Vandenberg, RJ; Lynch, JW; Dodd, PR (Journal of Biological Chemistry, 2010)
The glial transporter excitatory amino acid transporter-2 (EAAT2) is the main mediator of glutamate clearance in brain. The wild-type transporter (EAAT2wt) forms trimeric membrane complexes in which each protomer functions autonomously. Several EAAT2 variants are found in control and Alzheimer-diseased human brains; their expression increases with pathological severity. These variants might alter EAAT2wt-mediated transport by abrogating membrane trafficking, or by changing the configuration or functionality of the assembled transporter complex. HEK293 cells were transfected with EAAT2wt; EAAT2b, a C-terminal variant; or either of two exon-skipping variants: alone or in combination. Surface biotinylation studies showed that only the exon-7 deletion variant was not trafficked to the membrane when transfected alone, and that all variants could reach the membrane when co-transfected with EAAT2wt. Fluorescence resonance energy transfer (FRET) studies showed that co-transfected EAAT2wt and EAAT2 splice variants were expressed in close proximity. Glutamate transporter function was measured using a whole cell patch clamp technique, or by changes in membrane potential indexed by a voltage-sensitive fluorescent dye (FMP assay): the two methods gave comparable results. Cells transfected with EAAT2wt or EAAT2b showed glutamate-dependent membrane potential changes consistent with functional expression. Cells transfected with EAAT2 exon-skipping variants alone gave no response to glutamate. Co-transfection of EAAT2wt (or EAAT2b) and splice variants in various ratios significantly raised glutamate EC(50) and decreased Hill coefficients. We conclude that exon-skipping variants form heteromeric complexes with EAAT2wt or EAAT2b that traffic to the membrane but show reduced glutamate-dependent activity. This could allow glutamate to accumulate extracellularly and promote excitotoxicity.